If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -10(-7) + -10y = 10 Multiply -10 * -7 70 + -10y = 10 Solving 70 + -10y = 10 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-70' to each side of the equation. 70 + -70 + -10y = 10 + -70 Combine like terms: 70 + -70 = 0 0 + -10y = 10 + -70 -10y = 10 + -70 Combine like terms: 10 + -70 = -60 -10y = -60 Divide each side by '-10'. y = 6 Simplifying y = 6
| 3x-11=5x-29 | | 3(v-1)+4v=3(v-1)+7 | | X^2+4xy-x^2=5 | | 5(4x+7)=-37+32 | | 1/2(x-11)=1/2 | | 9-7(x-3)=2x-10 | | 6(5x+1)=336 | | 3y-6=2(y+4) | | -27+3y=-9 | | 7-3(x-6)=5x-5 | | (1/4)y-(1/2)=(1/9) | | 4(6x+3)=300 | | 21-3x=4x | | 2x^6-10x^4+10=0 | | 4(6x+3)=3003 | | 4x=6.8 | | 4(x-1)-6=6x-2(4+x) | | 8(2x-6)=5(3x-7) | | f(x)=300x-5x^2+5 | | 3-4(x-3)=3x-12 | | 3(6+6x)=234 | | 8x+5y=1600 | | 30=x+.06x | | f(x)=300x-5x^2-5 | | F(0)=4x^2-9x+8 | | -40-(-53)= | | =300x-5x^2-5 | | 2a^4-5a^3-2a^2+10a-4=0 | | 2(x-7)+x=11 | | 5-x+2x-29=4x-34 | | (6*x)/2-6*5=(6*x)/3 | | 2(10+5x)=50 |